The Communicative Function of Non-Face Emoji "Folded Hands" in WhatsApp Interaction among Indonesians - Muhammad Muzakky; Didin Nuruddin Hidayat; Alek Alek (Langkawi: Journal of The Association for Arabic and English, 2021)
This study aimed to examine the communicative functions of the non-face “folded hands” emoji that Indonesians use in WhatsApp interactions. Using descriptive qualitative, the data were analysed through the social semiotic approach proposed by Lemke (1998),  the interactional sociolinguistic theory (Gumperz, 1982), and speech act theory. The data were taken from the messages that occurred naturally in several WhatsApp groups. It was re-transcribed and translated in English based on the theory by Dresner and Herring (2010). The findings revealed some functions of the non-face “folded hands” emoji in online communication. At the end of an utterance, it emphasizes message tone, politeness, and soft interaction. Furthermore, rather than this emoji expresses an emotion such as face emoji does, it performs illocutionary forces in communication such as thanking, apologizing, and asking.  It is also performed in situational interaction in which the relation of speaker and interlocutor has a formal relation such as teacher-students and leader-staffs. This empirical research added to computer-mediated discourse literature by analyzing the communicative function of folded hands emoji in written discourse. Practically, it might help users interpret the emoji as an abstract concept in the messages.